2020
DOI: 10.1038/s41467-020-17615-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipo-chitooligosaccharides as regulatory signals of fungal growth and development

Abstract: Lipo-chitooligosaccharides (LCOs) are signaling molecules produced by rhizobial bacteria that trigger the nodulation process in legumes, and by some fungi that also establish symbiotic relationships with plants, notably the arbuscular and ecto mycorrhizal fungi. Here, we show that many other fungi also produce LCOs. We tested 59 species representing most fungal phyla, and found that 53 species produce LCOs that can be detected by functional assays and/or by mass spectroscopy. LCO treatment affects spore germin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 71 publications
0
92
0
Order By: Relevance
“…LysM receptors j legume symbiosis j lipochitooligosaccharide signaling j receptor-ligand interaction j kinetic proofreading B acteria and fungi surrounding plants synthesize amphiphilic lipochitooligosaccharide (LCO)-signaling molecules consisting of a chitin backbone decorated with a large variety of substitutions at the terminal moieties including hydrophobic acyls at the nonreducing end (1)(2)(3). The selectivity and activation mechanisms of single-pass transmembrane receptors involved in deciphering between this myriad of extracellular signals is still unknown.…”
mentioning
confidence: 99%
“…LysM receptors j legume symbiosis j lipochitooligosaccharide signaling j receptor-ligand interaction j kinetic proofreading B acteria and fungi surrounding plants synthesize amphiphilic lipochitooligosaccharide (LCO)-signaling molecules consisting of a chitin backbone decorated with a large variety of substitutions at the terminal moieties including hydrophobic acyls at the nonreducing end (1)(2)(3). The selectivity and activation mechanisms of single-pass transmembrane receptors involved in deciphering between this myriad of extracellular signals is still unknown.…”
mentioning
confidence: 99%
“…Rush et al 41 observed that COs slightly enhance spore germination in Aspergillus fumigatus and pseudohyphae formation in Candida glabrata, albeit to a significantly more limited extent, compared to LCOs 40 . Further analyses will be necessary to investigate if analogous effects are also present in AM fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular domains mediate the recognition of ubiquitous and conserved MAMPs such as peptides derived from bacterial flagellin, chito-oligosaccharides, that are constituents of the cell wall or lipo-chitooligosaccharides. The latter two had formerly been associated with symbiosis (16) but their presence extends beyond symbiotic fungi (17). Changes in receptor complexes, often involving conserved co-receptors such as BAK1 or SOBIR1 can then result in elevated, or oscillating, concentrations of intracellular calcium and the activation of downstream kinase cascades to activate defense gene networks.…”
Section: Extra-and Intracellular Immunitymentioning
confidence: 99%